What's up with Whatsapp profile pictures and statuses ? a multimodal approach - Nyambo, Enock (Midlands State University, 2020)
The development of social networking sites as linguistic and communication platforms is rising across all age groups in Zimbabwe. Amongst a plethora of social networking sites such as Facebook and Twitter, WhatsApp is the most common in Zimbabwe. Consequently, this research examined the essence of WhatsApp profile pictures and statuses. The research was guided by four main objectives which are to: 1. Analyse the Significance of WhatsApp Profile Pictures and Statuses. 2. Explain the nature of WhatsApp Profile Pictures and Statuses. 3. Examine the messages portrayed by WhatsApp Profile Pictures and Statuses. 4. Evaluate the advantages and disadvantages of WhatsApp Profile Pictures and Statuses. Different scholars’ perspectives on social media semantics in general and WhatsApp profile pictures and statuses in particular were looked at. A case study qualitative design was used. It involved the administering of in-depth semi-structured interviews and focus group discussions as research instruments. Participatory observation complemented interviews and focus group discussions. Convenient sampling technique was used to select 60 respondents for the research. The participants in this study were the WhatsApp users (18-65 year olds) enrolled or recruited by Midlands State University (MSU) Harare Campus who were willing to participate in the study. The data was analysed using axial coding and comparative analysis. The study was informed by the multimodal discourse analysis theory. The research found out that WhatsApp profile pictures are linguistic communication affordances associated with the multimodal portrayal of identity, emotions, ideology, personality and events in one’s life. Opportunities and challenges were discovered and participants emphasized cultural awareness and caution as measures to mitigate cited challenges.